Mensuração do desempenho de environmental, social e governance – ESG e de inovação de empresas da construção civil no Brasil - Cruz, Pedro Lucas (2022)
In order that the Civil Construction sector continues leading global development, it becomes increasingly necessary to adopt innovative and sustainable practices to reduce the environmental impact intrinsic to its activities. The main objective of this dissertation is to measure and analyze the ESG and innovation performance of Civil Construction companies in Brazil. In addition, it has the specific objectives: to identify, through a Systematic Literature Review – RSL, the concept, models and indicators of ESG and innovation in the sector; analyze, measure and correlate the most used ESG and innovation indicators in the sector. As for the method, the present study is classified as qualitative and quantitative. For the qualitative stage, an RSL was developed, following the precepts of Denyer and Neely (2004), Ridley (2008) and Tranfield et al. (2003) and Bardin's (2011) content analysis method, as well as analysis of ESG reports from Brazilian Civil Construction companies listed on the B3 stock exchange. For the quantitative stage, a survey was applied to 120 companies classified as Brazilian builders and contractors from different states. The instrument proposed for the research, consisting of 47 questions with a Likert scale of applicability, was developed based on a vast theoretical basis, with emphasis on Kneipp (2020, 2021), Ribeiro (2017) and Favarin (2021), identifying relevant themes for elaboration of questions in the works of Arruda Castro (2016), Eilers et al. (2016), Banihashemi et al. (2017), Kavishe et al. (2019), Alexandrino (2020) and others. For the analysis of the results, descriptive, confirmatory, regression and correlation analyzes were applied. As a result, the research showed a strong correlation between ESG performance and the levels of innovation recorded in Civil Construction companies. In addition, there was a strong influence of organizational characteristics, such as size and location, on the performance of builders, developers and contractors. The ESG and innovation performances presented by the companies were low, showing gaps and opportunities for improvement in the applicability of practices and actions to improve performance in the proposed themes